Preparation method of porous PET (Polyethylene Terephthalate) film, product of porous PET film and PET product degradation method

By blending PET products with thermodynamic compatible amorphous components and performing porous treatment, a porous PET membrane with nano-scale slit holes was prepared, which solved the problem of difficulty in degrading PET products and significantly improved the bioenzyme degradation rate and efficiency.

CN119735852AActive Publication Date: 2025-04-01HANGZHOU NORMAL UNIVERSITY
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411893143.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-01
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

Existing PET products cannot be effectively degraded in nature, resulting in plastic pollution, and high crystallinity PET products are difficult to degrade. Traditional grinding/ball grinding methods cannot effectively improve degradation efficiency.

Method used

By physically mixing the PET product with thermodynamic compatible amorphous components, melt tableting, crystallization and extraction processes, a porous PET film with nanoscale slit holes is prepared as a substrate for bioenzyme degradation.

Benefits of technology

It significantly improves the ontological degradation rate of PET membrane by biological enzymes, overcomes the limitation that biological enzymes can only surface degrade in traditional PET products, reduces the crystallinity of PET, and improves the infiltration efficiency and degradation efficiency of biological enzymes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735852A_ABST
    Figure CN119735852A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a porous PET (Polyethylene Terephthalate) film, a product of the porous PET film and a PET product degradation method. The preparation method comprises the following steps: physically mixing a PET product to be recycled with a thermodynamically compatible amorphous component, and then melting and tabletting to prepare the blend film with the thickness of 1 mu m-1 mm. And extracting thermodynamically compatible amorphous components in the blended membrane by using a Soxhlet extraction method to prepare the porous PET membrane. The porous PET film prepared by the method is provided with continuous nano through holes which are mutually penetrated, the crystallinity is low, the infiltration of the biological enzyme in the porous PET film is facilitated, the body degradation is realized, the energy efficiency of degrading the PET product by the biological enzyme is greatly improved, and the energy consumption and the recovery loss of the PET product in the biological enzyme degradation process are effectively reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a preparation method of a porous PET film and a product thereof and a PET product degradation method. Background Art

[0002] Polyethylene terephthalate (PET) is widely used in food packaging and textiles due to its excellent physical and chemical properties, such as thermal stability, mechanical properties, chemical resistance, safety and non-toxicity. However, PET products cannot be effectively degraded in nature, so they have become an important source of plastic pollution. How to quickly and effectively complete the recycling and reuse of PET products is a focus of attention at present.

[0003] Bioenzymatic degradation is a PET recycling strategy with low energy consumption and high recovery yield, which has received widespread attention in recent years. PET degrading enzymes can act on the ester bonds in the PET molecular chain to break and depolymerize the PET chain. The terephthalic acid (TPA) monomers finally recovered can also be used as polymerization monomers to synthesize PET for recycling. To date, experts in the field of enzyme structural biology have discovered and extracted dozens of PET degrading enzymes, and improved the degradation efficiency of PET products by genetically modifying these degrading enzymes. Currently, the most active PET degrading enzyme can achieve nearly complete degradation of amorphous PET within 3.3 hours.

[0004] In addition to increasing the activity of PET degrading enzymes, structural modification of PET products is also a way to improve the efficiency of bioenzymatic degradation of PET products. PET products are usually solid sheets. If PET products are directly placed in bioenzymes for degradation, the bioenzymes can only act on the surface of the PET sheet to achieve surface degradation. Only after the surface layer is degraded can the internal surface layer continue to be degraded. This will cause the degradation rate to be limited by the low-energy characteristics of the surface of PET products (not easy to bond with other materials). Some researchers have improved the efficiency of bioenzymatic degradation by grinding / ball milling PET products. The inherent mechanism is to increase the contact area between the bioenzyme and the PET substrate and prolong the action time. However, grinding / ball milling will lead to an increase in the crystallinity of PET products (which is not conducive to degradation), and the significant reduction in the size of the PET substrate will not destroy the dense internal structure, so the degradation efficiency will still be affected by the low-energy characteristics of the PET surface. How to transform the bioenzymatic degradation of PET products from surface degradation to bulk degradation is the key to significantly improving the degradation rate of PET products, and it is also one of our goals for structural modification of PET products.

[0005] In addition, the degradation of high-crystallinity PET products is also a major problem. Although the currently reported biological enzymes can degrade amorphous and low-crystallinity PET products in a short period of time, their degradation ability for PET products with a crystallinity higher than 20% is very limited, or even unable to achieve degradation. Therefore, effectively reducing the crystallinity of PET degradation substrates is another goal of our structural modification of PET products. Summary of the invention

[0006] The object of the present invention is to provide a method for preparing a porous PET film and a method for degrading a PET product thereof in view of the deficiencies in the prior art.

[0007] To achieve the above object, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a method for preparing a porous PET film, specifically: Physically mixing the PET product with a thermodynamically compatible amorphous component at a temperature above 250°C to obtain a blend; The blend is melted and pressed at a temperature above 250°C, then transferred to a temperature above 180°C for crystallization for at least 1 minute, and finally cooled naturally at room temperature to obtain a fully crystallized blend film; A thermodynamically compatible amorphous component good solvent that does not dissolve PET is selected to fully extract and dry the fully crystallized blend film to obtain a porous PET film after structural modification pretreatment.

[0008] Preferably, the physical mixing is to add the PET product and the thermodynamically compatible amorphous component into a co-solvent, fully dissolve them at a temperature above room temperature, and remove the solvent.

[0009] Preferably, the physical mixing is to add the PET product and the thermodynamically compatible amorphous component into a mixing device and melt-mix the blended components.

[0010] Preferably, the thermodynamically compatible amorphous component includes at least one of polyarylate PAR and polyetherimide PEI.

[0011] Preferably, the mass ratio of the PET product to the thermodynamically compatible amorphous component is (0.01:100) to (100:0.01).

[0012] Preferably, the crystallinity of the PET product is higher than 20%.

[0013] In a second aspect, the present invention provides a porous PET film having nano-scale slit holes, which is prepared by the above method.

[0014] In a third aspect, the present invention provides a method for degrading PET products, specifically: The PET product to be recycled is prepared into a PET porous membrane by the above method, and then the PET porous membrane is used as an enzyme degradation substrate and PET hydrolase is added for degradation.

[0015] Preferably, the degradation solvent is a glycine buffer.

[0016] Preferably, the PET hydrolase is FAST-PETase-N212A / N277A, the degradation temperature is 50° C., and the pH is 9.

[0017] The beneficial effects of the present invention are at least: The present invention successfully prepares a PET porous membrane with a unique structure by physically mixing the PET product to be recycled with a thermodynamically compatible amorphous component, and then undergoing a series of processes such as melt pressing, crystallization, and extraction. The membrane has nanoscale slit holes with a length of 100-200nm and a width of 1-100nm, and the pore size can be regulated by changing the crystallization temperature. This nanoscale slit hole structure provides more entry channels for biological enzymes, allowing the biological enzymes to quickly infiltrate the interior of the PET membrane, thereby effectively overcoming the limitation that the biological enzymes in traditional PET products can only perform surface degradation, greatly promoting the biological enzymes' bulk degradation of the PET membrane, and significantly improving the biological enzyme degradation rate.

[0018] The special structure of the PET porous film of the present invention provides more contact interfaces and attachment points for enzyme molecules, increases the enzyme attackable sites per unit time, realizes bulk degradation of the PET film, and can effectively improve the degradation rate of the biological enzyme.

[0019] The PET porous pretreatment adopted in the present invention can reduce the crystallinity of PET and allow biological enzymes to enter the crystal region more easily, so that the degradation efficiency can be effectively improved.

[0020] The preparation of the PET porous film of the present invention only requires the use of common melt mixing equipment or simple solution treatment, and the industrial preparation is simple and has strong processability. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The following are scanning electron microscope photos of the PET porous membranes prepared in Examples 1 and 2, wherein (a) is Example 1 and (b) is Example 2.

[0022] Figure 2 The crystallinity data of the PET film products prepared in Comparative Examples 1 and 2 and Examples 1 and 2 are shown.

[0023] Figure 3 The enzymatic degradation rate data of the PET film products prepared in Comparative Examples 1 and 2 and Examples 1 and 2 are shown.

[0024] Figure 4 These are the degradation rate data of the PET film products prepared in Comparative Examples 1 and 2 and Examples 1 and 2 after the degradation is completed. DETAILED DESCRIPTION

[0025] The embodiments of the present invention will be described in detail below in conjunction with the embodiments and examples, but it will be appreciated by those skilled in the art that the following embodiments and examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified, proceed according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0026] It should be noted that: In the present invention, unless otherwise specified, all the embodiments and preferred implementation methods mentioned herein can be combined with each other to form a new technical solution.

[0027] In the present invention, unless otherwise specified, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.

[0028] Unless otherwise specified, the professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any method or material similar or equivalent to the described content may also be applied to the present invention.

[0029] As can be seen from the background technology, in order to transform the bio-enzymatic degradation of PET products from surface degradation to bulk degradation, the present invention proposes a porous PET film and its product and a PET product degradation method.

[0030] The present invention prepares a PET porous membrane as a substrate for bioenzyme degradation by blending the PET product to be recycled with a thermodynamically compatible amorphous component and then extracting it. The bioenzyme can achieve bulk degradation of the substrate through the continuous nano-through holes in the PET porous membrane, greatly improving the efficiency of enzyme degradation. In addition, the crystallinity of the PET porous membrane is significantly reduced compared to the PET product without structural modification, and the crystal structure is more conducive to the infiltration of the bioenzyme. Therefore, the present invention provides a method for quickly and efficiently recycling and reusing PET products by constructing a PET porous membrane, which is expected to be applied to the large-scale degradation and reproduction of PET products.

[0031] Therefore, on the one hand, at least one embodiment provides a method for preparing a porous PET film, specifically: Physically mixing the PET product with a thermodynamically compatible amorphous component at a temperature above 250°C to obtain a blend; The blend is melted and pressed at a temperature above 250°C, then transferred to a temperature above 180°C for crystallization for at least 1 minute, and finally cooled naturally at room temperature to obtain a fully crystallized blend film; A thermodynamically compatible amorphous component good solvent that does not dissolve PET is selected to fully extract and dry the fully crystallized blend film to obtain a porous PET film after structural modification pretreatment.

[0032] In one embodiment, the physical mixing is to add the PET product and the thermodynamically compatible amorphous component into a co-solvent, fully dissolve them at a temperature above room temperature, and remove the solvent.

[0033] In one embodiment, the physical mixing is to add the PET product and the thermodynamically compatible amorphous component into a mixing device and melt-mix the blended components.

[0034] According to the present invention, after the thermodynamically compatible amorphous component is blended with the PET product, the amorphous component is removed through subsequent melt-compression, crystallization and extraction steps, thereby leaving corresponding space in the PET matrix and forming continuous nano-through holes that penetrate each other. These nano-through holes provide a channel for the bioenzyme to quickly infiltrate the inside of the PET film, making it possible for the bioenzyme degradation to change from traditional surface degradation to bulk degradation, greatly improving the contact opportunity between the bioenzyme and the PET molecular chain, and thus improving the degradation rate. At the same time, the presence of the thermodynamically compatible amorphous component can interfere with the orderly arrangement of the PET molecular chain during the crystallization process. During crystallization, the amorphous component occupies a certain space, hindering the PET molecular chain from forming a tight and regular crystal structure, so that the crystallinity of the PET porous film finally prepared is significantly reduced. Finally, in the process of melt mixing or solution blending, the thermodynamically compatible amorphous component also plays a certain plasticizing or lubricating role. They can improve the melt fluidity of the PET product, make the blend easier to operate during processing such as melt compression, and help to form a uniform film structure. In a preferred embodiment, the thermodynamically compatible amorphous component includes at least one of polyarylate PAR and polyetherimide PEI; the mass ratio of the PET product to the thermodynamically compatible amorphous component is (0.01:100) to (100:0.01).

[0035] According to the present invention, the problem that PET products are difficult to degrade in nature is solved, among which the degradation of high-crystallinity PET products (crystallinity higher than 20%) is a major problem. Although high-crystallinity PET products are the focus of the present invention and the object of solving the problem of their bioenzyme degradation, the method of the present invention is also applicable to PET products with other crystallinity ranges.

[0036] On the other hand, at least one embodiment provides a porous PET film prepared by the above method. The porous PET film is a film with a thickness of 1 μm to 1 mm, and the film has a plurality of continuous through holes with a length of 100 to 200 nm and a width of 1 to 100 nm that penetrate each other, and the pore size can be regulated by changing the crystallization temperature. At the same time, the crystallinity of the porous PET film is less than 10%. These structural features allow the biological enzyme to quickly infiltrate the porous PET film and achieve bulk degradation of the porous PET film.

[0037] In another aspect, at least one embodiment provides a method for degrading a PET product, specifically: The PET product to be recycled is prepared into a PET porous membrane by the above method, and then the PET porous membrane is used as an enzyme degradation substrate and PET hydrolase is added for degradation.

[0038] The method of pre-treating PET products by porous structural transformation before bioenzymatic degradation effectively improves the energy efficiency of bioenzymatic degradation, thereby reducing the energy consumption and recycling loss of PET products during bioenzymatic degradation. The nano-scale slit pore structure of the porous PET film provides more entry channels for bioenzymes, allowing the bioenzymes to quickly infiltrate the interior of the PET film, thereby effectively overcoming the limitation that the bioenzymes in traditional PET products can only perform surface degradation, greatly promoting the bulk degradation of the PET film by bioenzymes, and significantly improving the bioenzymatic degradation rate. This special structure creates more contact interfaces and attachment points for enzyme molecules. Compared with ordinary PET products in solid sheet form, the number of sites that can be attacked by enzymes per unit time is greatly increased. The enzyme molecules can more fully contact the PET molecular chains and act on the lactone bonds, causing the PET chain to break and depolymerize, thereby achieving more efficient degradation. This feature enables the PET porous membrane of the present invention to exhibit excellent performance during bioenzymatic degradation, and can achieve a higher degree of degradation in a shorter time, effectively improving the recycling efficiency of PET products. Nano-scale slits significantly reduce the crystallinity of PET to less than 10%. Lower crystallinity means that the arrangement of PET molecular chains is looser and the crystal structure is more conducive to the infiltration of biological enzymes. Biological enzymes can more easily enter the crystal area and interact with PET molecular chains, thereby effectively improving the degradation efficiency. This is of great significance for solving the problem that high-crystallinity PET products are difficult to degrade, making it possible to achieve efficient degradation of high-crystallinity PET products (crystallinity higher than 20%) that were originally difficult to be degraded by biological enzymes, broadening the application scope of biological enzyme degradation of PET products.

[0039] For a melt mixing system, such as a PET / PAR blending system, the specific steps of the method are as follows: Step (1). Place PET and PAR in a vacuum drying oven at about 120° C. and dry until the weight remains unchanged; Step (2). Mix the dried PET and PAR and add them into a melt mixing device, wherein the mass ratio of the PET product to the PAR is (0.01:100) to (100:0.01), and melt mix them at a temperature above 250°C for 5 to 10 minutes; In a preferred embodiment, the mass ratio of PET to PAR is 1:1; In a preferred embodiment, the melt mixing temperature in step (2) is 270° C. and the mixing time is 5 min; The melt mixing equipment is a common industrial device such as an internal mixer, a single screw extruder, a twin screw extruder or an injection machine; Step (3) discharging the melt-mixed blend from the melt-mixing equipment and cooling it to room temperature; Step (4). The cooled blend is melt-pressed at a temperature above 250°C for 2 to 10 minutes, and transferred to a temperature above 180°C for crystallization for at least 1 minute to prepare a film of 10 μm to 1 mm; In a preferred embodiment, the melt tableting temperature is 270°C and the tableting time is 2 min; In a preferred embodiment, the crystallization temperature is 230°C and the crystallization time is 2h; Step (5). The film obtained in step (4) is extracted by Soxhlet extraction, the extracting solution is a good solvent for PAR, the heating temperature is controlled so that the extracting solution refluxes once every 6 to 8 minutes, the extraction time is 72 to 144 hours, and after the extraction is completed, it is taken out and dried overnight in a vacuum drying oven at 80°C to remove the residual solvent, thereby obtaining a PET porous membrane; In a preferred embodiment, the good solvent of PAR is chloroform, dichloromethane, carbon tetrachloride or acetone; Step (6). Take 5 g of the PET porous membrane obtained in step (5) as a bioenzyme degradation substrate, add 40 μL of FAST-PETase-N212A / N277A enzyme (5 μg / mL) to form an 800 mL mixture, and place it in a 50 mM glycine, pH 9.0 buffer for degradation test at a degradation temperature of 50° C. Determine the amount of product generated every 24 hours of degradation, and calculate the degradation rate after the degradation is completed by the total product generation.

[0040] The amount of the product generated was determined and analyzed by high performance liquid chromatography (HPLC), wherein the analytical column was an InertSustain C18 column (4.6×250mm, 5μm), the mobile phase was methanol / phosphate (20 mM, pH2.5), the flow rate was 1mL / min, the detection wavelength was 254nm, the elution condition was 0~15min, and the methanol linear gradient was 35%~70%.

[0041] For a solution blending system, such as a PET / PEI blending system, the specific steps of the method are as follows: Step (1). Mix PET and PEI and dissolve them in their co-solvent, the mass ratio of PET product to PEI being (0.01:100) to (100:0.01); In a preferred embodiment, the solvent is dichloroacetic acid or a phenol / tetrachloroethane mixed solvent (volume ratio is 60 / 40); In a preferred embodiment, the solvent selected is dichloroacetic acid; In a preferred embodiment, the mass ratio of PET to PEI is 7:3; Step (2) washing the mixed solution of PET and PEI with deionized water to precipitate the PET / PEI mixed solute; Step (3). The PET / PEI mixed solute precipitated by washing is placed in a vacuum oven at ~80°C for drying to obtain a PET / PEI blended powder; Step (4). The dried blended powder is melt-pressed at a temperature above 250°C for 2 to 10 minutes, and transferred to a temperature above 180°C for crystallization for at least 1 minute to prepare a film of 10 μm to 1 mm; In a preferred embodiment, the melt tableting temperature is 270°C and the tableting time is 5 min; In a preferred embodiment, the crystallization temperature is 230°C and the crystallization time is 2h; Step (5). The film obtained in step (4) is extracted by Soxhlet extraction, the extracting solution is a good solvent for PEI, the heating temperature is controlled so that the extracting solution refluxes once every 6 to 8 minutes, the extraction time is 72 to 144 hours, and after the extraction is completed, it is taken out and dried overnight in a vacuum drying oven at 80°C to remove the residual solvent, thereby obtaining a PET porous membrane; In a preferred embodiment, the good solvent of PEI is methanol, ethanol, dichloromethane, chloroform or acetone; Step (6). Take 5 g of the PET porous membrane obtained in step (5) as a bioenzyme degradation substrate, add 40 μL of FAST-PETase-N212A / N277A enzyme (5 μg / mL) to form an 800 mL mixture, and place it in a 50 mM glycine, pH 9.0 buffer for degradation test at a degradation temperature of 50° C. Determine the amount of product generated every 24 hours of degradation, and calculate the degradation rate after the degradation is completed by the total product generation.

[0042] The amount of the product generated was determined and analyzed by high performance liquid chromatography (HPLC), wherein the analytical column was an InertSustain C18 column (4.6×250mm, 5μm), the mobile phase was methanol / phosphate (20mM, pH 2.5), the flow rate was 1mL / min, the detection wavelength was 254nm, the elution condition was 0~15min, and the methanol linear gradient was 35%~70%.

[0043] Some typical embodiments that embody the features and advantages of the present invention are described in detail below. It should be understood that the present invention can have many variations in different schemes without departing from the scope of the present invention. And the descriptions and illustrations therein are essentially for illustration only, not for limiting the present invention.

[0044] The PAR used in the following examples was produced by Unikita Co., Ltd. of Japan, with the model number being U100; and the PEI was produced by Sigma-Aldrich Co., Ltd. of the United States, with the product number being 700193.

[0045] Example 1 The high crystallinity PET flakes to be recycled (e.g., crystallinity of about 25%) and PAR were dried in a vacuum drying oven at 120°C overnight; 35 g of PET flakes to be recycled and 35 g of PAR were added to an internal mixer in sequence. The temperature of the internal mixer was 270°C and the rotor speed was 20 rpm / min. The internal mixer was kneaded for 2 min. The rotor speed was then increased to 50 rpm / min and the internal mixer was kneaded for 5 min before discharging the material and cooling it to room temperature. The melt-kneaded mixture was hot-pressed in a hot press at 280° C. for 2 min to form a 300 μm film; The hot-pressed film was transferred to 200 °C for crystallization for 2 h to complete the crystallization; The crystallized film is subjected to Soxhlet extraction using a good solvent of PAR, the heating temperature is controlled so that the extractant refluxes once every 6 to 8 minutes, the extraction time is 72 to 144 hours, and after the extraction is completed, the film is taken out and dried overnight in a vacuum drying oven at 80° C. to remove the residual solvent, thereby obtaining a PET porous film; Take 5g of the above PET porous membrane as a bioenzyme degradation substrate, add 40μL FAST-PETase-N212A / N277A enzyme (5μg / mL) to form an 800mL mixture, and place it in a 50mM glycine, pH 9.0 buffer for degradation test, and the degradation temperature is 50°C. Determine the amount of product generated every 24h of degradation, and calculate the degradation rate after the degradation is completed by the total product generation.

[0046] Example 2 Take 14 g of high crystallinity PET flakes to be recycled (e.g., crystallinity of about 25%) and 6 g of PEI, add them into 250 mL of a co-solvent in sequence, and stir overnight at 50-80° C. until they are completely dissolved; The above solution is washed with deionized water to precipitate the PET / PEI mixed solute; The washed PET / PEI mixed solute was placed in a vacuum oven at 80°C for drying to obtain a PET / PEI mixed solute powder; The mixture powder was hot pressed in a hot press at 290°C for 5 min to form a 300 μm film; The hot-pressed film was transferred to 220 °C for crystallization for 2 h to complete the crystallization; The crystallized film is subjected to Soxhlet extraction using a good solvent of PEI, the heating temperature is controlled so that the extractant refluxes once every 6 to 8 minutes, the extraction time is 72 to 144 hours, and after the extraction is completed, the film is taken out and dried overnight in a vacuum drying oven at 80° C. to remove the residual solvent, thereby obtaining a PET porous film; Take 5g of the above PET porous membrane as a bioenzyme degradation substrate, add 40μL FAST-PETase-N212A / N277A enzyme (5μg / mL) to form an 800mL mixture, and place it in a 50mM glycine, pH 9.0 buffer for degradation test, and the degradation temperature is 50°C. Determine the amount of product generated every 24h of degradation, and calculate the degradation rate after the degradation is completed by the total product generation.

[0047] Comparative Example 5g of high crystallinity PET sheet to be recycled (e.g., crystallinity of about 25%) was used as a bioenzyme degradation substrate, 40μL FAST-PETase-N212A / N277A enzyme (5μg / mL) was added to form a mixture of 800mL, and placed in a 50mM glycine, pH 9.0 buffer for degradation test, and the degradation temperature was 50°C. The amount of product generated per 24h of degradation was determined, and the degradation rate after the degradation was completed was calculated by the total product generation. This comparative example simulates the traditional PET sheet processing method (hot pressing crystallization only), which is compared with the PET porous membrane preparation process in the embodiment (including structural modification steps such as blending and extraction with thermodynamically compatible amorphous components), which further proves that the present invention can significantly improve the bioenzyme degradation performance of PET products through a special porous structure modification pretreatment method.

[0048] By comparing the various data of Examples 1 and 2 with those of the comparative example during the degradation process (such as Figure 1 Middle (a) Figure 1 Middle (b), Figure 2 , Figure 3 , Figure 4 As shown in the figure, it can be clearly seen that the PET porous membrane prepared by the present invention has obvious advantages in crystallinity, enzyme degradation rate and degradation rate after degradation. Examples 1 and 2 have good nano-scale slit pore structure ( Figure 1 ), Examples 1 and 2 can reduce the original crystallinity higher than 20% to a lower crystallinity ( Figure 2 In addition, their degradation rate (reflected by the degradation mass of PET substrate within 48h) and the degradation rate of PET substrate after degradation are much higher than those of the control group ( Figure 3 , 4 ), indicating that through the method of the present invention, the crystal structure is more conducive to the infiltration of biological enzymes, and is conducive to the full contact between the enzyme and the substrate, thereby achieving the bulk degradation of the PET substrate, and greatly improving the degradation rate and degradation rate. The method of the present invention effectively improves the energy efficiency of biological enzyme degradation of PET products by preparing a PET porous membrane with a unique structure, reduces energy consumption and recovery losses, and provides an efficient and feasible solution for the recycling of PET products. At the same time, the preparation process of the present invention is simple, the industrial applicability is strong, and it has good application prospects and promotion value.

[0049] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a porous PET film, characterized in that: The method comprises: Physically mixing the PET product with a thermodynamically compatible amorphous component at a temperature above 250°C to obtain a blend; The blend is melted and pressed at a temperature above 250°C, then transferred to a temperature above 180°C for crystallization for at least 1 minute, and finally cooled naturally at room temperature to obtain a fully crystallized blend film; A thermodynamically compatible amorphous component good solvent that does not dissolve PET is selected to fully extract and dry the fully crystallized blend film to obtain a porous PET film after structural modification pretreatment.

2. The method according to claim 1, characterized in that: The physical mixing is to add the PET product and the thermodynamically compatible amorphous component into a co-solvent, fully dissolve them at a temperature above room temperature, and remove the solvent.

3. The method according to claim 1, characterized in that: The physical mixing is to add the PET product and the thermodynamically compatible amorphous component into a mixing device and melt-mix the blended components.

4. The method according to any one of claims 1 to 3, characterized in that: The thermodynamically compatible amorphous component includes at least one of polyarylate PAR and polyetherimide PEI.

5. The method according to any one of claims 1 to 3, characterized in that: The mass ratio of the PET product to the thermodynamically compatible amorphous component is (0.01:100) to (100:0.01).

6. The method according to any one of claims 1 to 3, characterized in that: The crystallinity of the PET product is higher than 20%.

7. A porous PET film having nano-scale slit holes, characterized in that: The method is prepared by any one of claims 1 to 6.

8. A method for degrading PET products, characterized in that: The method comprises: The PET product to be recycled is prepared into a PET porous membrane by the method according to any one of claims 1 to 6, and then the PET porous membrane is used as an enzyme degradation substrate and PET hydrolase is added for degradation.

9. The method according to claim 8, characterized in that: Glycine buffer was used as the degradation solvent.

10. The method according to claim 8, characterized in that: The PET hydrolase used was FAST-PETase-N212A / N277A, with a degradation temperature of 50°C and pH=9.

Citation Information

Patent Citations

  • Preparation method for porous film with controllable apertures

    CN105131327A

  • Preparation method of porous polyethylene film

    CN106565977A

  • Preparation method of self-assembled antistatic polyester porous membrane with high heat conductivity

    CN107880291A

  • Polyvinylidene fluoride hierarchical pore film with island structure and preparation method thereof

    CN110615903A

  • Modification method of polyethylene glycol terephthalate and application thereof in enzymolysis process

    CN113698742A